الدلالة الزمنية في الأفعال ومشبهاتها والأدوات في ترجمة عبدالله باسميح للآيات القرآنية إلى الملايوية : دراسة وصفية تحليلية - نور العظيمة بنت محمد سعود Nurul Azimah Mohd Soud
The Malay language is devoid of Arabic verb forms, their analogies, and tools whose use in the sentence affect the expression of the readers and listeners, and carries various temporal connotations. Therefore, the translators of the Noble Qur’an into Malay may face great challenges in translating these verb forms, their analogies and tools, as they cannot find the exact equivalent translation despite their skill and competence, and therefore they resort to compensatory strategies. This study seeks to understand the dimensions and axes of this problem. The study followed the descriptive analytical approach by searching for the temporal connotation, which is the different meaning of every use of Arabic verb forms, their analogies, and tools, of the ancients and contemporaries and the impact of the Qur’anic context on it. The study also provides examples of verbs and their analogies and tools that carry expressive meanings and various temporal connotations to analyse their translation presented by Abdullah Basmeh. Including the connotation of the use of the perfect verb, the imperfect verb, and the active participle, the connotation of the use of the negation tools of ‘ma’, ‘lam’, ‘la’ and ‘lan’ as well as the tool of future tense which are ‘sin and saufa’, and the connotations of the use of ‘kaana’. The study then ascertains opinions about the equivalence of the Malay translation and the issue of loss of meaning. This study aimed to identify the temporal connotations that cause a problem for translators, the methods used to confront that problem, and their impact on the temporal significance of the target text. The study concluded that the forms of verbs and their analogies and tools that carry expressive meanings and various temporal connotations in the Qur’anic verses are not translated into Malay except by omitting the time reference, using the time reference ‘akan’ or some other additions. However, (kaana) may be translated as ‘adalah’, while its translation has been left out elsewhere. The study also found that all translation methods used cancel the reference to the expressive meaning, and this may affect the delivery of the content of the Qur’anic verses to the target text reader. The study suggests conducting contrastive studies in the translation of (‘idh’, ‘idha’) and (‘in’, ‘law’) with its conjunction with the perfect and imperfect verb, and (kaana) with all its uses in the Qur’anic verses into Malay, to make it a book that Malays can refer to get used to the language of the Qur’an, especially the temporal connotations of the Qur’anic verses.